2014
DOI: 10.1002/anie.201402950
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of a Microporous Conductive Polymer Based on a Metal–Organic Framework Thin Film

Abstract: A new approach to preparing 3D microporous conductive polymer has been demonstrated in the electrochemical synthesis of a porous polyaniline network with the utilization of a MOF thin film supported on a conducting substrate. The prepared porous polyaniline with well-defined uniform micropores of 0.84 nm exhibits a high BET surface area of 986 m(2) g(-1) and a high electric conductivity of 0.125 S cm(-1) when doped with I2, which is superior to existing porous conducting materials of porous MOFs, CMPs, and COF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 97 publications
2
89
0
Order By: Relevance
“…It is important to note that, after doping, the crosslinked polymer displayed a higher conductivity, most likely because iodine can now easily enter the open network structure yielding a higher amount of oxidized DTT species. In general, these values are comparable with other reports derived from electrical conductivity measurements of organic porous networks 5962…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to note that, after doping, the crosslinked polymer displayed a higher conductivity, most likely because iodine can now easily enter the open network structure yielding a higher amount of oxidized DTT species. In general, these values are comparable with other reports derived from electrical conductivity measurements of organic porous networks 5962…”
Section: Methodssupporting
confidence: 92%
“…A suspension of FeCl 3 (0.18 g, 1.1 mmol) in dry CHCl 3 (20 mL) was stirred for 10 min under nitrogen atmosphere. Then, a solution of DTTPh 2 ‐Th 4 (0.138 g, 0.2 mmol) in dry CHCl 3 (10 mL) was added to this suspension and the mixture was stirred for one day 59. The precipitate was filtered and washed with THF, CHCl 3 , H 2 O, and MeOH, subsequently.…”
Section: Methodsmentioning
confidence: 99%
“…. . cloth, and then following this, PANI was deposited by an electrochemical process [107]. In this study, carbon cloth serves as the substrate on which the active material is formed, and is able to be retained as the current collector for device construction.…”
Section: Additional Materials After Mofs Are Preparedmentioning
confidence: 99%
“…Because of their high porosities and tunable structural properties, they have wide functional applications in terms of catalysis [5,6], gas storage [7,8], sensors [9], biomedicine [10], and so on. Apart from the use of MOFs as crystalline porous materials, the utilization of MOFs as a precursor for metal/metal oxide nanoparticle-embedded carbon frameworks has been researched actively in recent years [11,12,13,14,15,16]. The subject has become of particular interest for functional applications such as catalysis, gas storage materials, anode materials for lithium-ion batteries, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The subject has become of particular interest for functional applications such as catalysis, gas storage materials, anode materials for lithium-ion batteries, etc. [13,14,15,16]. After the report by Q. Xu et al on the carbonization of MOF-5 [11], various methods have been reported to synthesize materials that contain metal/metal oxide nanoparticle-embedded porous carbon matrix from MOF precursors [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%